2010
DOI: 10.2166/wst.2010.462
|View full text |Cite
|
Sign up to set email alerts
|

Removal of manganese ions from synthetic groundwater by oxidation using KMnO4 and the characterization of produced MnO2 particles

Abstract: The aim of this study is to investigate the conditions for the removal of manganese ions from synthetic groundwater by oxidation using KMnO(4) to keep the concentration below the allowed level (0.05 mg/L). The process includes low-level aeration and addition of KMnO(4) in a Jar test system with Mn(2 + ) concentration of 0.50 mg/L, similar to that of natural groundwater in Taiwan. Different parameters such us aeration-pH, oxidant dose, and stirring speed were studied. Aeration alone was not sufficient to remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Experiments were carried out using a standard jar test system, similar to those reported in Phatai et al [9]. Jar tests were done in triplicate and the average was obtained.…”
Section: Batch Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were carried out using a standard jar test system, similar to those reported in Phatai et al [9]. Jar tests were done in triplicate and the average was obtained.…”
Section: Batch Studymentioning
confidence: 99%
“…Therefore, an optimum amount of KMnO 4 is determined in order to reduce Mn 2+ and Fe 2+ to a concentration below the MCL. The optimum conditions such as pH and stirring speed obtained from the previous study [9] would be utilized in the removal of Fe 2+ and Mn 2+ in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The Increase in rate of removal of metal ions with increasing adsorption time could be due to greater contact between the surface of the adsorbent and metal ions. Also, the existence of a large number of active surface sites on active carbon and the rapid diffusion of metal ions from the bulk of the solution to the adsorbent surface [28]. The adsorption was very rapid initially and large amount of Fe 3+ as well as Mn 2+ removed in first 50 min.…”
Section: Contact Time Effectmentioning
confidence: 99%
“…It has been reported that stoichiometric addition of KMnO 4 is not necessary for complete oxidation of some metals in solution (Phatai et al 2010;Roccaro et al 2006;US EPA 1999). Roccaro et al (2006) found that a pH adjustment to 8.5 coupled with the addition of half the stoichiometric amount of KMnO 4 was sufficient to reduce dissolved Mn from about 1.5 to \50 lg/L.…”
Section: Manganese Oxidation and Removalmentioning
confidence: 99%
“…Roccaro et al (2006) found that a pH adjustment to 8.5 coupled with the addition of half the stoichiometric amount of KMnO 4 was sufficient to reduce dissolved Mn from about 1.5 to \50 lg/L. Phatai et al (2010) also demonstrated that a half stoichiomteric dose of KMnO 4 successfully reduced the dissolved concentration of Mn A B Fig. 4 Tl (lg/L) (a), Mn (lg/L) (b), and pH with time for actual MIW under three KMnO 4 conditions: quarterstoichiometric, halfstoichiometric, and stoichiometric (based on initial Mn concentration in actual MIW of 13 mg/L); error bars show the standard deviation for the triplicate analyses from 0.5 to \50 lg/L at pH 9.0.…”
Section: Manganese Oxidation and Removalmentioning
confidence: 99%